Politics, religion and ideas in seventeenth- and eighteenth-century Britain essays in honour of Mark Goldie - Champion, Justin 1960-2020; Coffey, John 1969-; Harris, Tim 1958-; Marshall, John 1961- (The Boydell Press, 2019)
This volume traces the evolution of Whig and Tory, Puritan and Anglican ideas across a tumultuous period of British history, from the mid-seventeenth century through to the Age of Enlightenment